Management Financing In Improving The Quality Of Education - Togi Van Jaya; Nathanael Sitanggang; M. Joharis Lubis (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2022)
This study aims to determine the management of education financing in relation to efforts to improve the quality of education. This study focuses on the study of how the influence of financial management of education on quality of educationof the PKBM PELITA, Deli Serdang Regency. This research uses qualitative methods based on descriptive studies. Data collection techniques using observation, interviews, and documentation studies. Data analysis was performed using the Miles and Huberman model stages, namely data reduction, data presentation, and conclusion drawing. The data validity test used triangulation and member crosscheck. The results showed that the management of educational finance had been done well 1) the process of budgeting according to the procedure; 2) sources of finance obtained from several sources of funds; 3) the constraining factor in the management of educational finance belongs to the flow of disbursement of funds long enough; 4) supervision and accountability in the educational finance is going well; and 5) Foundations, principals, vice principals, treasurers, school committees, teachers and UPTD Education involved in the education finance management process